Liquidity Measurement and Stock Returns - Wei, Rui (2013)
This dissertation tests the liquidity premium theory by using both cross-sectional and time-series model. Results show that cross-sectional illiquidity is positively related to stock return, and the expected liquidity has positively influence on market excess return over time. Also, contemporaneous unexpected liquidity is different from expected liquidity; it is negatively related to market excess return over time. The liquidity proxies used here are turnover rate which is the times of stock trades during a specific time period; and ILLIQ which is the daily absolute stock return to the trading volume in dollars. By grouping up our sample by size, results shows that smaller stocks are affected more than larger stocks by liquidity. There is no January effect shown in our results. The famous 2007-2008 financial crisis data does not have a significant effect on the result as well.